2014
DOI: 10.4103/0301-4738.129783
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral intraocular pressure lowering effect of prostaglandin analogues

Abstract: Background:Though the use of prostaglandin analogues (PGA) for reduction of intraocular pressure (IOP) has shown a marked increase, studies evaluating the contralateral effects of PGA are limited.Aims:To evaluate if PGA treatment in one eye has an effect on the IOP of the untreated fellow eye.Design:Retrospective study.Materials and Methods:Thirty patients of open-angle glaucoma with no previous antiglaucoma treatment underwent 24-hour diurnal IOP phasing. They subsequently were started on a uniocular trial wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Clinical studies have previously reported previously that monocular treatments can affect fellow eyes,30–32 meaning that comparison of measures between treated and fellow eyes cannot serve as valid controls, and that population norms are the most useful comparators. Given that both the treated and fellow eyes showed a slower progression rate compared with previous reports, there may also be a similar sympathetic response in the fellow untreated eye.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have previously reported previously that monocular treatments can affect fellow eyes,30–32 meaning that comparison of measures between treated and fellow eyes cannot serve as valid controls, and that population norms are the most useful comparators. Given that both the treated and fellow eyes showed a slower progression rate compared with previous reports, there may also be a similar sympathetic response in the fellow untreated eye.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if contralateral ocular hypotension is caused by TM flowing into the contralateral eye via the plasma, then TM would also affect the iris sphincter muscle, meaning the contralateral eye must cause miosis in dogs. Other possible mechanisms proposed for the contralateral effects are the centrally mediated effect of a systemically absorbed drug and a consensual reaction related to changes in IOP in the treated eye [ 15 , 42 ]. Our results of a contralateral ocular hypotensive effect might have been caused by these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…One eye has been chosen for each patient to minimize the bias that might be induced by the cross-over effect of the drugs and the variability of patients’ response to treatment. 14…”
Section: Methodsmentioning
confidence: 99%